PEMBUATAN GAME BE A HACKER MENGGUNAKAN APLIKASI MACROMEDIA FLASH 8 - Asnawati Asnawati; Yupianti Yupianti (Jurnal Media Infotama, 2011)
Flash is a multimedia graphics and animation program that can be used interactively to create exciting web applications, but Macromedia as the developer of this program continues to enrich the capabilities of this program. Macromedia Flash 8 has a lot of changes in appearance, Filter, Blend Mode and other facilities. This software is increasingly popular as the ability to surf the web in addition to multimedia devices, it is no wonder if the flash to take an important role as one of the world of software support content. While the purpose of writing this thesis is to find out how to be a hacker game creation using Macromedia Flash 8 application. problems in this study is "How to Be A Hacker Game Making Applications Using Macromedia Flash 8". The results of the study is the Game Be A Hacker, who designed using Macromedia Flash 8 application. This application can be used by the manufacturer to perform the addition of characters, editing colors and shapes, while the user can be used as an entertainment to fill the empty time. Keywords: Game Be A Hacker, Macromedia Flash